2020
DOI: 10.2139/ssrn.3707893
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Costs versus Actual Benefits of Demographic Self-Disclosure in Online Support Groups

Abstract: Millions of U.S. adults join online support groups to attain health goals, but the social ties they form are often too weak to provide the support they need. What impedes the strengthening of ties in such groups? We explore the role of demographic differences in causing the impediment and demographic self-disclosure in removing it. Using a field study of online quit-smoking groups complemented by three laboratory experiments, we find that members tend to hide demographic differences, concerned about poor socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Our findings highlighted three other behaviors related to COVID-19. The first behavior was limited openness behavior (Pechmann et al , 2021). During the COVID-19 pandemic, the number of hate crimes targeting specific ethnic groups increased significantly (Gover et al , 2020).…”
Section: Finding and Discussion – Spar-4-slr Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings highlighted three other behaviors related to COVID-19. The first behavior was limited openness behavior (Pechmann et al , 2021). During the COVID-19 pandemic, the number of hate crimes targeting specific ethnic groups increased significantly (Gover et al , 2020).…”
Section: Finding and Discussion – Spar-4-slr Frameworkmentioning
confidence: 99%
“…During the COVID-19 pandemic, the number of hate crimes targeting specific ethnic groups increased significantly (Gover et al , 2020). Consequently, minority groups felt uncomfortable revealing their status and identity and limiting their public behavior (Pechmann et al , 2021). The second behavior was social connectedness and do-it-yourself (DIY) (Kirk and Rifkin, 2020).…”
Section: Finding and Discussion – Spar-4-slr Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, Pechmann et al (2021) investigated the role support groups play in facilitating goals regarding why consumers join those groups. In the context of online communities, where self‐disclosures may be a way to build trust in the community, the authors consider how self‐disclosures regarding differences between group members are made.…”
Section: Reconceptualizing Prosocial Behavior As Intersocialmentioning
confidence: 99%
“…Whereas Pechmann et al (2021) reported positive interpersonal outcomes in online communities, Pundak et al (2021) found that consumers can also engage in public shaming of wrongdoers. This observation raises interesting questions such as whether actions that benefit more people by discouraging bad behavior but hurt an individual are prosocial, when are these actions prosocial, and whether such actions can be considered prosocial when other actions could also have discouraged bad behaviors.…”
Section: Reconceptualizing Prosocial Behavior As Intersocialmentioning
confidence: 99%